Effects of Liquid Probiotics (Lactobacillus sp.) on Microflora Balance, Enzyme Activity, Number and Surface Area of the Intestinal Villi of Broiler - Muhammad Izzuddiyn; Woro Busono; Osfar Sjofjan (Graduate Program, 2018)
The aims of this study were to determine the effects of probiotic liquid as feed additive on productivity, microflora balance, enzym activity, number and surface of intestinal villi of broiler. This study was used experimental method with Completely Randomized Design (CRD) on 144 Day Old Chicks (DOC) Lohman strain, which divided into 4 treatment groups and 6 replications. The treatment was the basal feed without the addition of liquid probiotic (P0); basal feed with 0,2 v/w liquid probiotic (P1); basal feed with 0,4 v/w liquid probiotic (P2) and basal feed with 0,6 v/w liquid probiotic (P3). Liquid probiotic containing composition of Lactobacillus sp. 1,4x1010 cfu/mLl. Data were analyzed using a CRD followed by the Duncan Multiple Range Test. The results showed that liquid probiotic (Lactobacillus sp.) as food additive give the significant effect (P<0,05) to the number of intestinal villi, showed no significant effect (P>0,05) to protease and lipase activity. It`s showed significant effect (P<0,01) to total plate count (TPC) of lactid acid bacteria, Salmonella sp., Eschericia coli, surface of intestinal villi.. The result were concluded that the higher concentration of liquid probiotics in feed the higher microflora balance, protease and lipase activity, number and surface of intestinal villi. Decreasement of Salmonella sp. and Eschericia coli TPC. As suggestion, a liquid probiotics (Lactobacillus sp.) 0.6 v/w in feed can produce the higher performance.Keywords: broilers, intestinal characteristics, liquid probiotic